Contribución de la contabilidad a la educación financiera, en el tema del ahorro (Revista "Boletín el Conuco", 2020)
Accounting as social discipline, away from the business context and orients its object of study towards education. This research article presented in paragraphs the contribution of accounting to financial education.The problem of the research study is part of economic education and financial-EEF, in particular the issue of savings; the concern by develop this study, has as antecedent them results of them tests PISA of the 2012, where the students Colombian were below the half of them countries participating, occupying the last since in the know financial.For the purpose of this research is structure a frame reference, supported in the following theories: didactic, strategies didactic and the didactic for the approach financial; the conceptual elements that articulate this framework are: finance, savings, financial habits for children and teaching mediation. The sources consulted are the curricular guidelines for math fifth grade of the MEN, document No. 26 of the MEN and Asobancaría; the guidelines of the tests know of the ICFES and the PEI, of the school context of study.The methodological horizon, is supported in the research perspective action-IA; precisely because of its social approach and character expressed in practical, participatory nature, qualitative, critical and interpretative which make it suitable for research.The purpose of the research is it contribution with a strategy didactic and its mediation for the education financial in the theme of the saving to children and girls of fifth of basic primary.
Keywords: saving; accounting; financial education; teaching strategy and educational mediation; JEL M41; M49; P43